Venous thromboembolism in children with Hodgkin lymphoma – A population-based study in Sweden, Finland, and Denmark - Giertz, Mia; Aarnivala, Henri; Michelsen, Sascha W.; Björklund, Caroline; Grönroos, Marika; Hjalgrim, Lisa L.; Huttunen, Pasi; Niinimäki, Riitta; Pöyhönen, Tuuli; Raittinen, Päivi; Ranta, Susanna; Svahn, Johan E.; et al. (Elsevier Ltd, 2025)
Background:
Children and adolescents with Hodgkin lymphoma (HL) are susceptible to developing venous thromboembolism (VTE) due to several predisposing factors such as cancer itself, central venous catheter use, mediastinal mass, and glucocorticoid therapy, yet reports on the topic are scarce.
Aim:
To study incidence, risk factors, and treatment of VTE, and the use of thromboprophylaxis, in a retrospective clinical study on pediatric HL.
Methods:
Children under 18, diagnosed with HL 2005–2019 in Sweden, Denmark, and Finland were included. Data on patient characteristics, treatment, thrombotic events and follow up were collected from patients' medical records.
Results:
A total of 490 children were identified and data were assessed for 489. The cumulative 2-year incidence of VTE was 8.1 % (42/489). Older age at diagnosis (p = 0.004), mediastinal involvement (p = 0.024), and HL stage III + IV (p = 0.036) were significant risk factors for VTE. Children over 15 with mediastinal mass and HL stage III or IV had a 1-year cumulative incidence of VTE of 18 % and a nearly three-fold risk of developing VTE compared to all other patients (OR 2.94, 95 % CI 1.47–5.88, p = 0.002). The majority (39/42; 92.9 %) were treated with low-molecular-weight heparin. Four (9.5 %) patients developed post-thrombotic syndrome. Thromboprophylaxis was given to 18/489 (3.7 %) patients with HL, two of whom developed VTE.
Conclusion:
VTE is a common complication in adolescents treated for HL with large tumor burden at diagnosis. Prospective studies should focus on identifying patients who would benefit from thromboprophylaxis.